State-Sponsored Qur’anic Exegesis and Interreligious Relations: A Comparative Study of Egypt, Saudi Arabia, and Indonesia - Aksin Wijaya; Ahmad Zainal Abidin; Muh Syaifudin (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
This article explores how three state-sponsored Qurʾānic exegeses-al-Muntakhab (Egypt), al-Muyassar (Saudi Arabia), and al-Wajiz (Indonesia)-conceptualize the essence of religion and articulate models of interreligious relations. These tafsirs are selected because they are produced by official state institutions and therefore reflect the ideological orientations and religious policies of their respective governments. Employing a qualitative comparative method, this study combines theoretical hermeneutics to reconstruct the historical meanings of the tafsirs with philosophical hermeneutics to assess their relevance for contemporary Indonesian society. The analysis focuses on three dimensions: methodological identity, the conception of religion in terms of unity and diversity, and approaches to interreligious relations encompassing dialogue, social harmony, and cooperation. The findings demonstrate that although the three tafsirs share fundamental theological premises-such as monotheism, prophetic continuity, and moral universality-they differ significantly in interpretive orientation. Al-Muntakhab reflects a rational-moderate Azhari tradition, al-Muyassar adopts a scripturalist Salafi framework with exclusivist tendencies, while al-Wajiz advances an inclusive and accommodative hermeneutic aligned with Indonesia’s pluralistic ethos and the principle of Bhinneka Tunggal Ika. This study argues that state-sponsored tafsir functions not merely as a religious text but as an ideological instrument that shapes public religious discourse. When oriented toward justice, equality, and interreligious cooperation, such tafsir can contribute meaningfully to religious moderation in plural societies.